Serum Soluble CD89-IgA Complexes Are Elevated in IgA Nephropathy without Immunosuppressant History. (16th January 2020) - Wu, Haiting; Wang, Xiaoyan; Yang, Zhe; Zhao, Qing; Wen, Yubing; Li, Xuemei; Zhang, Wei; Gao, Ruitong
Abstract : Purpose. CD89 (Fc α RI), the receptor of IgA, can shed from cells to form complexes with IgA in serum and is supposed to participate in the pathogenesis of IgA nephropathy (IgAN). There are contradictory results on their utility in clinical practice. This study is aimed at investigating whether sCD89-IgA complexes can help in the diagnosis or evaluation of the disease. Methods . A sandwich ELISA was established using anti-CD89 as a capture antibody and HRP-conjugated anti-IgA as a detection antibody. This method was used to measure serum levels of sCD89-IgA complexes in IgAN patients without immunosuppressant history and healthy subjects. Correlations between serum levels of sCD89-IgA complexes and disease severity were analyzed. Results . Serum sCD89-IgA complexes increased with age (P < 0.001 ). IgAN patients had higher sCD89-IgA complex levels compared with age- and gender-matched normal healthy individuals (P < 0.001 ). Serum sCD89-IgAN significantly predicted IgAN diagnosis (AUC = 0.762 (0.640-0.883), P < 0.001 ). But sCD89-IgA complexes did not correlate with baseline clinical manifestations, oxford classification, or renal function deteriorate speed. Conclusions . Serum sCD89-IgA complexes can guide diagnosis of IgAN in patients without immunosuppressant history, but provide limited help in clinicopathologic prediction.